1. The problem statement, all variables and given/known data Show that the integral from -1 to 1 of p(x)*log|z-x| dx equals log|z - sqrt(z^2 -1)| / 2, where p(x) = 1 / (pi*sqrt(1-x^2)) 2. Other information This topic comes from Chebyshev interpolation. p(x) is the Chebyshev density. 3. The attempt at a solution The best idea I could come up with was to use z = x + iy and substitute that into log|z-x| to get log|x+iy-x| = log|iy| = log(y) since |iy| = sqrt(0^2 + y^2) = sqrt(y^2) = y. That left me with just one term with an x to integrate. Then I used trig substitution of x = sin(theta) to have the integral become: integral from -pi/2 to pi/2 of log(y)/pi d(theta). That left me with an answer of just log(y) which is clearly not right, or at least not in the form that should be. I think my approach to the integration is completely off.